Re-engineering the City: Platform Ecosystems and the Capture of Urban Big Data - Barns, Sarah (Frontiers in Sustainable Cities, 2020)
Today's digital platforms occupy sites of growing strategic significance in the daily lives of cities. Acting as infrastructures of urban exchange, platform services institute basic match-making capabilities between mobile subjects, whether for transportation, shopping, accommodation, dating, or, simply, public discourse. As is increasingly recognized, the nature of value exchange traded via these platforms extends beyond their immediate domain of service provision, whether transportation or accommodation, for example, to wider “data ecosystems” of users, producers, and consumers. It is the conditions instituted by platform services to govern data ecosystems that are the focus of this article and are, I argue, of critical importance to how big data can be leveraged in ways that expand new frontiers of urban science and more broadly, urban sustainability policy. The rise in platform urbanism means that urban big data are not simply as a diagnostic tool for monitoring and evaluating complex urban behaviors but can be co-opted in ways that actively engineers the scaling of data-driven platform services and their myriad codependencies. These conditions present significant challenges not only to informational policy but increasingly also to urban governance settings, where platform-mediated interactions facilitate powerful but unevenly shared territories of urban intelligence.